Access cookbook - Getz, Ken (O'Reilly, 2004)
"Not a reference book, and not a tutorial either, the new second edition of the highly regarded Access Cookbook is an uncommonly useful collection of solutions to problems that Access users and developers are likely to face as they attempt to build increasingly complex applications. Although using any single 'recipe' in the book will more than pay back the cost of the book in terms of both hours saved and frustration thwarted, Access Cookbook, Second Edition is much more than a handy assortment of cut-and-paste code. Each of the 'recipes' examine a particular problem--problems that commonly occur when you push the upper limits of Access, or ones that are likely to trip up a developer attempting to design a more elegant Access application--even some things you never knew Access could do. The authors then, in a clear, accessible, step-by-step style, present the problems' solution. Following each "recipe" are insights on how Access works, potential pitfalls, interesting programming techniques that are used in the solution, and how and why the solution works, so you can adapt the problem-solving techniques to other similar situations. Fully updated for Access 2003, Access Cookbook, Second Edition is also one of the first books to thoroughly explore new support for .NET managed code and XML. All of the practical, real-world examples have been tested for compatibility with Access 2003, Windows XP, and Windows Server 2003. This updated new edition also covers Access and SharePoint, Access and SmartTags, Access and .NET; and Access and XML."--Provided by publisher.